Pengoptimalan Tingkat Persediaan Bahan Baku Fire Tube Boiler dengan analisis Markov Chain - Astuti, Murti; Latifah, Nuril (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
Controlling material stock becomes important problem that faced by the company because controlling it supports production process continually. In applaying material is efforted in order getting cost of supplier more law as possible. PT. Indomarine is one kind of company that produces tube involving two type are fire tube and water tube, in which the primary material is tube and plat. In dealing the consumen needs, the company should give amount materials so that the production will be continually, and the consumer will satisfy. Having more suplies like that is caused by accepting fluctually needs, than causes less supplier optimumly and less in cost too. Based on fenomenon above, so in this research will mucstigate the methods that will be counted the number of material asking.